Analisa Bangkitan Perjalanan di Kawasan Perumahan Terhadap Jalan Raya Pekayon, Kota Bekasi - Sari, Fauziya Bagawat; Savitry, Reny (Jurnal Wilayah dan Kota, 2025)
Bekasi City is one of the hinterland areas of DKI Jakarta Province. As a result, residential land use causes a lot of traffic congestion, greatly affecting the level of service on Jalan Raya Pekayon as an adaptive traffic road. An increase in the number of vehicles, if not matched by an increase in road infrastructure, will result in congestion problems caused by the attraction of housing around Jalan Raya. This study aims to determine how Jalan Raya Pekayon's housing growth has affected the area's traffic issues. The coefficient of determination (R square) is 0.470, or 47%, based on the trip generation calculation and existing road section results. The result is Y Loan = 0.737 Y + 0.079 X1 + 0.013 X2 + 0.271 X3 + 0.124 X4. More and more travel movements generated from housing cause loading on the Pekayon Highway section. As a result, the degree of saturation on Monday in the afternoon peak hour reaches 0.75. With a 10-year projection, the degree of saturation in the section will reach 1.02 in 2033, which means that the section has exceeded the safe limit.